1997
DOI: 10.1074/jbc.272.13.8539
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Interaction of Fas and FAP-1

Abstract: Fas (APO-1/CD95) and its ligand have been identified as important signal-mediators of apoptosis (1). The structural organization of Fas (APO-1/CD95) indicates that it is a member of the tumor necrosis factor receptor superfamily, which also includes the p75 nerve growth factor receptor (2), the T-cellactivation marker CD27 (3), the Hodgkin-lymphoma-associated antigen CD30 (4), the human B cell antigen CD40 (5), and T cell antigen OX40 (6). Genetic mutations of both Fas and its ligand have been associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 43 publications
8
65
0
Order By: Relevance
“…Recent studies have identi®ed several molecules related to CD95 signal transduction. Yanagisawa et al (1997) reported that Fas-associated phosphatase-1 (FAP-1) bound to the negative regulatory domain of CD95, leading to the inhibition of CD95-induced apoptosis in DLD-1 cells. This ®nding suggests that the very ®rst step of CD95 signaling is blocked by FAP-1 in DLD-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identi®ed several molecules related to CD95 signal transduction. Yanagisawa et al (1997) reported that Fas-associated phosphatase-1 (FAP-1) bound to the negative regulatory domain of CD95, leading to the inhibition of CD95-induced apoptosis in DLD-1 cells. This ®nding suggests that the very ®rst step of CD95 signaling is blocked by FAP-1 in DLD-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of other proteins that interfere with Fas signalling include FAP-1, which is an inhibitory Fas-binding protein that interacts with the Cterminal 15 amino acids of the regulatory domain of the Fas receptor (Sato et al, 1995). FAP-1 has been identified in cultured colon carcinoma cells (Yanagisawa et al, 1997), and its expression was reported to be highest in cell lines and tissues that are relatively resistant to Fas-mediated cytotoxicity (Sato et al, 1995). However, others have shown that cell lines extremely sensitive to Fas-induced apoptosis (HUT78, SKW6.4) expressed high levels of FAP-1, whereas a Fas-resistant line was completely negative for FAP-1 mRNA (Boe R ; Peter et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…reduced expression of the Fas antigen; Moller et al, 1994), or elevated expression of genes that promote cellular survival (Bcl-2; Bedi et al, 1995) or inhibit essential signalling pathways (e.g. FAP-1; Yanagisawa et al, 1997). We have therefore defined the cellular sensitivity to Fas-mediated apoptosis in 10 human colon carcinoma cell lines and have determined the expression of genes known to regulate the function of the Fas signalling pathway in the induction of Fas-dependent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FAP-1 is also known as protein-tyrosine phosphatase, nonreceptor-type, 13 (PTNP13) and was found to associate with the carboxy terminal 15 amino acids of human Fas receptor [150]. In vitro inhibition of the interaction between FAP-1 and Fas using synthetic peptides demonstrated that the amino acid motif SLV, found at the carboxy terminus of the Fas receptor, was both sufficient and necessary for binding to FAP-1 [151]. Mouse Fas receptor does not contain this C-terminal motif and does not interact with either mouse FAP-1 (PTP-BL) or human FAP-1 when overexpressed in cells [152].…”
Section: Modulators Of Fas Receptor and Fas Ligand Expressionmentioning
confidence: 99%